Dilemmas of "biometric nationality" : migration control, biometric ID technology and political mobilisation of migrants in West Africa - Iwuoha, Victor; Doevenspeck, Martin (Territory, Politics, Governance, 2023)
Erschienen in Band 13, 3, 2025, S. 279-304